Sistema informático administrativo contable con aplicación móvil para la Empresa Crédito Miguelito Jr - Burgos Rodríguez, Oscar Rigoberto (2015)
The completion of this research, allowed developing the Accounting Administrative Information System with Mobile Application with a commitment to automate the information handled by the company JR Credit Miguelito. This system was developed in order to provide solutions to failures that occur to fulfill these functions manually, tasks and activities that are true in that company. To provide solutions to the flaws found accurately, and methodological, the general objective and specific objectives proposed, which is rightly made. For its development, the methodology took DUM as it allowed the development of applications based on an evolutionary and incremental approach to develop the application structure solution was raised, by focusing on user needs; so it was possible to write the report in computer terms, which allowed its programming; the constraint that the system will be in their access, which consist of a main screen where it will require a login and password, which will be administered in the system. This will allow better control and access security thereof. Program coding to be applied and evidence in order to verify the application of finishing with the maintenance program, which will be implemented to the extent that the system used was performed. For system design tools such as Visual Studio .Net and C# is a very broad application, language is used in a variety of mobile devices were used. The system operational database SQL Server and today is the database server more popular relational databases by making the design and programming of relational database type, the program is used as SQL server through which multiple users can be connected and used at the same time. Finally I mention paradimg is a visual UML CASE tool market, which is very comprehensive and easy to use, cross-platform support and provides excellent facilities for interoperability with other applications. Once completed all proposed development project, concluded that it was feasible to achieve the same, to the accounting system that will allow administrative control of the company, which effect you may be subject to adjustments, have been produced according to the new requirements that have a future in the process.